Application of immunotherapy in advanced non-small cell lung cancer with hypertension: a multicenter retrospective analysis - Yuan, Jingyi; Lei, Kaixin; Kong, Quanling; Chang, Tao; Gu, Xinhang; Wang, Juan; He, Li-na; Gan, Jiadi; Chen, Bojiang (Frontiers in Oncology, 2025)
ImportanceImmune checkpoint inhibitors (ICIs) have become the standard treatment for advanced non-small cell lung cancer (NSCLC). However, their prognostic role in NSCLC patients remains controversial. Hypertension (HTN) is an important risk factor for many cancers, but the pathogenesis underlying HTN in relation to cancer prognosis remains unclear.ObjectiveWe aimed to investigate the possible association between HTN and prognosis in advanced NSCLC patients.Data sourcesData on advanced NSCLC patients receiving immunotherapy at stages IIIb, IIIc or IV were included.Study selectionMulticenter retrospective studies and trials reporting the use of immunotherapy were included. Main outcomes and measures: Progression-free survival (PFS) and overall survival (OS) were analyzed using Cox proportional hazards models and were estimated by the Kaplan-Meier method. Subgroup analysis on NSCLC hypertensive patients was pre-planned and was presented in the form of Forest Plot. Statistical software utilized for all analyses included statistical analysis system (SAS) V.9.4 and R version 4.2.2 (R Foundation for Statistical Computing).ResultsBetween January 2016 and June 2024, 1175 NSCLC patients receiving immunotherapy were enrolled, with 219 (18.6%) classified as hypertensive group and 956 (81.4%) classified as non-hypertensive group. Neutrophil count and ECOG = 2 showed a significant association with OS in univariate analysis (HR = 0.69, 95%Cl: 0.51 - 0.92, P = 0.012, and HR = 1.02, 95%Cl: 1.00 to 1.03, P = 0.008 respectively). In multivariate analysis, ECOG = 2 was significantly correlated with OS (HR = 0.73, 95%Cl: 0.54 to 0.98, P = 0.037) and PD - 1/PD-L1 had significant association with PFS (HR = 1.27, 95%Cl: 1.00 to 1.61, P = 0.050). OS was found significantly longer in non-hypertensive group than in hypertensive group (P = 0.049). No baseline indicator was found significant correlated with the survival prognosis of patients receiving immunotherapy in subgroup analysis.Conclusion and relevanceThe non-hypertensive group was associated with a lower risk of mortality than hypertensive group. In subgroup analysis, no baseline indicator was observed a significant correlation with survival prognosis on OS and PFS in hypertensive patients. Our findings provided an important prognostic factor to improve the prognosis of advanced NSCLC patients receiving immunotherapy. Prospective randomized trials are needed to further validate these findings.